DETERMINAN PERILAKU MANAJEMEN KEUANGAN PADA UMKM DI KELURAHAN BENDA BARU KECAMATAN PAMULANG TANGERANG SELATAN : Untuk Mahasiswa UPN VETERAN JAKARTA - Muhammad Irvan Nur, (2020)
This research aims to determine the influence of financial literacy and financial inclusion on the conduct of financial management on micro, small and medium enterprises in the new village of Benda, South Tangerang Regency. The population in this study is the all actors micro, small, and medium enterprises in the area of new Benda that amounted to 400 MSMES. With a sample number of 200 respondents, using the probability sampling method. Data collection is used through the deployment questionnaire. The data analysis technique used is the method of analysis of PLS (Partial Least Square). The results showed that financial literacy and financial inclusion positively influenced the behavior of financial management